2020
DOI: 10.13057/biodiv/d211033
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Genetic variation of Coelogyne pandurate, C. rumphii and their hybrids based on RAPD markers

Abstract: Abstract. Hartati S, Muliawati ES. 2020. Short Communication: Genetic variation of Coelogyne pandurata, C. rumphii and their hybrids based on RAPD markers. Biodiversitas 21: 4709-4713. One effort to increase the genetic diversity of orchids is by crossing. This research aims to assess the genetic variation of a hybrid orchid obtained by crossing Coelogyne pandurata and C. rumphii and their hybrids based on RAPD markers. In this research, both parents were analyzed in three replications, while the hybrid was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The phylogenetic tree (Figure 3) also showed that all Coelogyne from Indonesia such as C. mayeriana from Kalimantan, C. asperata from West Kalimantan have close evolutionary relationship then followed with C. pandurata from East Kalimantan that classified in the same subclade. This result is in agreement with phenetic taxonomy that has been done previosly in morphology comparison of each species from Indonesia (Hartati et al 2019;Hartati & Muliawati 2020). However, the tree are not representative for the separation of orchids originating from Asia, such as C. fimbriata and C. ovalis which should have close relationship (Jiang et al 2020) but located far apart in the phylogenetic tree constructed with rbcL.…”
Section: Resultssupporting
confidence: 84%
“…The phylogenetic tree (Figure 3) also showed that all Coelogyne from Indonesia such as C. mayeriana from Kalimantan, C. asperata from West Kalimantan have close evolutionary relationship then followed with C. pandurata from East Kalimantan that classified in the same subclade. This result is in agreement with phenetic taxonomy that has been done previosly in morphology comparison of each species from Indonesia (Hartati et al 2019;Hartati & Muliawati 2020). However, the tree are not representative for the separation of orchids originating from Asia, such as C. fimbriata and C. ovalis which should have close relationship (Jiang et al 2020) but located far apart in the phylogenetic tree constructed with rbcL.…”
Section: Resultssupporting
confidence: 84%
“…Further research to determine the molecular characteristics using RAPD (Random Amplified Polymorphic DNA) showed that analysis has successfully detected genetic variation of ♀ C. rumphii, ♂ C. pandurata, and their F1 hybrids. The orchid parents and their F1 hybrid have a similarity range of 16-100 % (Hartati and Muliawati 2020).…”
Section: Morphological Characterization Of Phaius Orchidsmentioning
confidence: 99%
“…The first contained only C. pandurata as the male parent, while the second comprised both C. rumphii as the female parents and all the ten hybrids. This indicated that maternal inheritance in the intergeneric hybridization between both orchid species occurred (Hartati & Muliawati, 2020).…”
Section: Resultsmentioning
confidence: 93%